The Role of Islamic Finance, Workers, and Added Value in the Agromaritime Sector on Economic Growth: A Study of Indonesia, Malaysia, and Brunei Darussalam - Tajul 'Ula; Juli Dwina Puspita Sari; Putri Ulifas Sahira; Erne Suzila Kassim (AL-MUZARA'AH, 2026)
The agromaritime sector faces various problems that hinder its potential to contribute optimally to economic growth. This study aims to analyze the role of Islamic finance sharing in the agromaritime sector, agricultural sector labor, and the added value of the agromaritime sector on economic growth in Indonesia, Malaysia, and Brunei Darussalam from 2019Q1 to 2023Q4 using the Autoregressive-Distributed Lag (ARDL) panel data model. The results of the analysis revealed that all independent variables showed a significant impact on economic growth in the long and short term. Islamic finance is able to provide alternative financing to encourage the agromaritime sector that supports inclusive economic activities. In addition, labor in the agricultural sector also plays a negative significant role on economic growth, indicating that improving the quality and quantity of labor in this sector can accelerate economic growth. The added value of the agromaritime sector has proven to contribute positively to economic growth. These findings underscore the importance of integrating Islamic finance with the development of the agromaritime sector and improving the quality of labor to achieve sustainable economic growth.